Somanathapura, Keshava temple, Western garbhagriha outer wall, carving of the Mohini avatara of Vishnu; Hoysala architecture - Lawrence Rodrigues (Jio Institute, 2021)
Image courtesy: Lawrence Rodrigues - www.yatrikaone.com